Intranasal esketamine as therapeutic option: a case report of an adolescent with treatment resistant depression - Skala, Katrin; Doganay, Kamer; Eder, Harald; Mairhofer, Dunja; Neubacher, Katrin; Plener, Paul L. (Frontiers in Psychiatry, 2023)
Depression is among the most common mental health disorders worldwide and treatment resistant depression represents a major challenge for both patients and clinicians. In recent years ketamine has received attention as an antidepressant agent, showing potential in TRD in adults. Scarce attempts have been made in treating adolescent TRD with Ketamine and none of these has used intranasal application. We here describe a case of a 17 year old student suffering from TRD that has undergone treatment with Ketamine 28mg nasal spray (Spravato). As symptoms showed only insignificant improvement (GAF, CGI, MADRS), treatment was prematurely discontinued. Although this report is rather unfavorable, Ketamine might still be a promising substance in treating TRD in adolescents. questions about safety of ketamine use in the rapidly developing brains of adolescents still remain unanswered. A next step would be to consider short term RCTs for adolescents with TRD.